Community Empowerment Through Education in Optimizing Human Resources and Natural Resources in the Village of Pematang Lalang - Imelda, Fatwa; Santosa, Heru (Talenta Publisher, 2023)
Background: KKN (Real Work Course) is one of the courses taken by final semester students as field practice. Objective: This activity aims to provide a learning experience. Method: This Community Service Program was carried out in Pematang Lalang Village, Sei Percut Tuan District, Deli Serdang Regency. This activity is carried out for 1 full month which is divided into 6 stages of activities, namely field surveys, permits for carrying out activities, problem analysis, planning, implementation and evaluation of activities. Activities that carry the theme of implementing community empowerment through education in optimizing HR (Human Resources) and SDA (Natural Resources). The focus of this activity is carrying out 4 priority activities in the fields of education, social culture, agriculture, and health. The result of this activity is that students are able to analyze problems into a plan and carry out structured planning in accordance with the expected achievements. Conclusion: Community service activities provide many benefits for students and the community where this activity takes place.